'A world with universal literacy': The role of libraries and access to information in the UN 2030 Agenda. (June 2016) - Bradley, Fiona
In September 2015, after more than three years of negotiations and intense involvement from many stakeholders, including the International Federation of Library Associations and Institutions (IFLA), the Member States of the United Nations adopted the post-2015 Development Agenda to succeed the Millennium Development Goals, Transforming Our World: The 2030 Agenda for Sustainable Development . This paper outlines and reflects on the key steps in IFLA's campaign and the importance of coalitions and national advocacy to realise the inclusion of access to information, universal literacy, public access to information and communication technology, and cultural heritage in the UN 2030 Agenda.